The Islamic Fundamentalism Based on Karen Armstrong's Perspective and Its Implications for The Identification of Fundamentalism Groups in Indonesia - Neli Rahmah; Nelmaya Nelmaya (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
One of the developments at the end of the twentieth century was the emergence of a militant piety popularly called